Optimizing ablation duration using dormant conduction to reveal incomplete isolation with the second generation cryoballoon: A randomized controlled trial - Keçe, Fehmi (J Cardiovasc Electrophysiol, 2019)
INTRODUCTION: Efficacy of cryoballoon ablation depends on balloon‐tissue contact and ablation duration. Prolonged duration may increase extracardiac complications. The aim of this study is to determine the optimal additional ablation duration after acute pulmonary vein isolation (PVI). METHODS: Consecutive patients with paroxysmal AF were randomized to three groups according to additional ablation duration (90, 120, or 150 seconds) after acute PVI (time‐to‐isolation). Primary outcome was reconnection/dormant conduction (DC) after a 30 minutes waiting period. If present, additional 240 seconds ablations were performed. Ablations without time‐to‐isolation <90 seconds, esophageal temperature <18°C or decreased phrenic nerve capture were aborted. Patients were followed with 24‐hour Holter monitoring at 3, 6, and 12 months. RESULTS: Seventy‐five study patients (60 ± 11 years, 48 male) were included. Reconnection/DC per vein significantly decreased (22%, 6% and 4%) while aborted ablations remained stable (respectively 4, 5, and 7%) among the 90, 120, and 150 seconds groups. A shorter cryo‐application time, longer time‐to‐isolation, higher balloon temperature and unsuccessful ablations predicted reconnection/DC. Freedom of atrial fibrillation was, respectively, 52, 56, and 72% in 90, 120, and 150 seconds groups ( P = 0.27), while repeated procedures significantly decreased from 36% to 4% ( P = 0.041) in the longer duration group compared to shorter duration group (150 seconds vs 90 seconds group). In multivariate Cox‐regression only reconnection/DC predicted recurrence. CONCLUSION: Prolonging ablation duration after time‐to‐isolation significantly decreased reconnection/DC and repeated procedures, while recurrences and complications rates were similar. In a time‐to‐isolation approach, an additional ablation of 150 seconds ablation is the most appropriate.